An Agri-Food Systems Analysis to Establish a Supportive Environment for Kenya’s Flour Blending Policy - Melesse, Mequanint B. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Kenya’s forthcoming national flour blending policy mandates the incorporation of at least 10% of traditional high-value crops, such as sorghum and millet, into maize flour. This policy represents a significant shift in the country’s food system, with the potential to drive increased demand for these drought-tolerant crops, promote agricultural diversification, and enhance food security. Taking an agri-food systems perspective, this study provides a critical analysis of the policy, identifying key constraints, knowledge gaps, and leverage points necessary for its successful implementation.